A New Approach to E-Learning (E-Web Class) (International Journal of Engineering and Computer Science, 2017)
Student- Teacher relationship has evolved over the WEB CLASS. Through the use of internet, the interaction between student and teacher has increased. So through our project we will create a classroom portal which will provide students effective and interactive learning and at the same it will reduce the work of teachers. Our portal is a new approach of classroom learning. It provides an option for the teachers to upload teaching videos which are related to the topic taught in the class. It provides an opportunity for the students to ask individual doubts in the chat option. This feature is helpful for the students who are afraid to ask doubts in the class. Virtual education is an emerging concept. Here the classes are not taken face-to-face in a classroom but through an electronic medium as a substitute. These virtual classrooms are gaining importance every day and very soon they are going to be an integral part of our world. As the number of Internet access points are growing rapidly, E-Learning is also gaining a new peak. This electronic medium serves best for dissemination of information. E-Learning is proving itself as a boon for students especially for the disabled who are not able to go and attend the lectures. All these emphases the need for developing an Open Source software that can be used to generate rich multimedia presentation for E-Learning.